Collision Warning in Vehicular Networks Based on Quantum Secure Multiparty Computation - Rahmani, Zeinab; Barbosa, Luis S.; Pinto, Armando N. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2022: Anais do II Workshop de Comunicação e Computação Quântica, 2022)
Quantum Secure Multiparty Computation (QSMC) is a technology that takes the advantage of quantum features allowing multiple parties to communicate in a secure and efficient manner while preserving their privacy. Using QSMC technology, we implement a collision warning use case in which vehicles can freely broadcast information while preserving the privacy of their confidential data. We integrate two quantum technologies namely Quantum Key Distribution (QKD) and Quantum Oblivious Key Distribution (QOKD) with the Malicious Arithmetic Secure Computation with Oblivious Transfer (MASCOT) protocol to implement a secure and efficient QSMC platform. This quantum approach significantly improves efficiency and security when we compare it with the classical implementation as both used quantum technologies (QKD and QOKD) are robust against quantum computer attacks.